Mengintegrasikan Kecerdasan Emosional, Kecerdasan Spiritual Dan Kecerdasan Buatan Dalam Praktik-Praktik Manajemen Sumber Daya Manusia Pada Organisasi Bisnis - iskandar, iskandar (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
With the increasingly complex and dynamic business world, the integration of emotional intelligence (EQ), spiritual intelligence (SQ), and artificial intelligence (AI) into human resource management (HRM) practices offers a holistic approach to improving workplace effectiveness and well-being. Emotional intelligence plays a vital role in managing interpersonal relationships, communication, and conflict management, which are crucial for effective leadership and teamwork. Spiritual intelligence supports the search for meaning and purpose in work, creating an organizational culture that aligns with personal and collective values. Artificial intelligence, on the other hand, automates processes, provides data-driven analytics, and improves operational efficiency through cutting-edge technology. Integrating these three intelligences can create a more productive, innovative, and fulfilling work environment. This article examines the basic theories of each intelligence and explains how their application in HRM practices can yield significant benefits to organizations.